La legislación franquista frente al cómic femenino (1938-1977) [Tema Central] - Rodríguez Moreno, José Joaquín (2020)
General Franco’s dictatorship imposed publications for children and teenagers a strict censorship system, which generated an important limitation for authors and editors of comic books. This article analyses –through the legislation of the Boletín Oficial del Estado, interviews and theoretical texts published during the dictatorship– who were the people in charge of creating the regulations and supervising the contents, and what objective they were looking after in the case of female teen comics, which were publications aimed at female readers.